2021
DOI: 10.1002/acn3.51443
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary review of therapeutic and regenerative management of intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) remains a common and debilitating form of stroke. This neurological emergency must be diagnosed and treated rapidly yet effectively. In this article, we review the medical, surgical, repair, and regenerative treatment options for managing ICH. Topics of focus include the management of blood pressure, intracranial pressure, coagulopathy, and intraventricular hemorrhage, as well as the role of surgery, regeneration, rehabilitation, and secondary prevention. Results of various phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 104 publications
(208 reference statements)
1
5
0
Order By: Relevance
“…Early intervention measures should include controlling systolic blood pressure within the range of 140 mmHg, correcting coagulopathy if indicated, and evaluating the need for surgical intervention. 16 Our study also revealed that in the SMM group of patients with basal ganglia hemorrhage, more than half of the patients remained severely disabled and unable to independently perform daily activities even after 6 months of onset. However, this proportion was relatively lower in patients with cerebral lobe hemorrhage.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Early intervention measures should include controlling systolic blood pressure within the range of 140 mmHg, correcting coagulopathy if indicated, and evaluating the need for surgical intervention. 16 Our study also revealed that in the SMM group of patients with basal ganglia hemorrhage, more than half of the patients remained severely disabled and unable to independently perform daily activities even after 6 months of onset. However, this proportion was relatively lower in patients with cerebral lobe hemorrhage.…”
Section: Discussionsupporting
confidence: 61%
“…[14][15] The prognosis of lobe and cerebellar hemorrhage is significantly better than that of brainstem and basal ganglia hemorrhage, with the highest proportion of coma and mortality observed in brainstem hemorrhage patients. [15][16][17][18] Currently, it remains unclear whether ANP has the same therapeutic effect on SICH in different locations. The purpose of this study was to investigate different locations of SICH separately, randomly assigning patients into two groups: the standard medical management (SMM) group and the combined ANP as well as medical management group (ANP group) to comparing the outcomes of these two management approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) is one of the most dangerous subtypes of stroke and affects more than 1 million people annually [ 1 , 2 ]. Despite extensive research into ICH pathology, a clinically approved neuroprotective treatment remains elusive [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the prevalence of ICH in young is increasing, and hypertension is the main cause of ICH in populations of Asia young adults [3], which has imparted a heavy social and economic burden. Although there is a great deal of attention focused on the development of e ective treatment for ICH, there is still a lack of available Class I Level A treatment modalities for ICH patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the prevalence of ICH in young is increasing, and hypertension is the main cause of ICH in populations of Asia young adults [ 3 ], which has imparted a heavy social and economic burden. Although there is a great deal of attention focused on the development of effective treatment for ICH, there is still a lack of available Class I Level A treatment modalities for ICH patients [ 4 ]. Currently, the available treatment options for ICH employ supportive care management and/or surgical removal of hematoma [ 5 ], both of which are not ideal for significantly ameliorating ICH.…”
Section: Introductionmentioning
confidence: 99%